Development of Microemulsions Containing Ruean-Mhoon-Nok Remedy Extract and Evaluation for Skin Irritation in Healthy Volunteers - Taingthum, Atchanika; Chakkavittumrong, Panlop; Kanokkangsadal, Puritat; Sakpakdeejaroen, Intouch (Trends in Sciences, 2026)
Ruean-Mhoon-Nok (RMN), a Thai traditional remedy, has been used topically to treat skin inflammatory disorders, including dermatitis and psoriasis. Previously, the ethanolic extract of RMN and its bioactive compound, hydroxychavicol, demonstrated promising in vitro anti-inflammatory activity by inhibiting NO and IL-6 production. Therefore, this study aimed to develop a stable microemulsion capable of enhancing skin penetration of the RMN extract and to evaluate its potential for skin irritation in healthy volunteers. Two RMN microemulsion formulations were prepared, consisting of an oil phase (Capryol® 90) combined with surfactants (Polyglyceryl-4 caprate or PEG-6 caprylic/capric glycerides) and a co-surfactant (Transcutol® P) at a weight ratio of 1:2. These microemulsions had mean droplet sizes of less than 100 nm and carried a negative surface charge. Furthermore, they remained stable after nine heating-cooling storage cycles. In vitro skin permeation studies showed that the RMN microemulsions were able to penetrate the skin and release hydroxychavicol, achieving a maximum cumulative permeation of 26% over 8 h. In healthy volunteers, the RMN microemulsions were well tolerated, showing no signs of irritation at the maximum dose of 3% RMN extract. In conclusion, the RMN microemulsions are highly promising formulations that warrant further investigation for their efficacy and safety in clinical applications. HIGHLIGHTS Two RMN microemulsion formulations were successfully prepared, consisting of an oil phase (Capryol® 90) combined with surfactants (Polyglyceryl-4 caprate or PEG-6 caprylic/capric glycerides) and a co-surfactant (Transcutol® P) at a weight ratio of 1:2. The RMN microemulsions had mean droplet sizes of less than 100 nm and carried a negative surface charge. In vitro skin permeation studies showed that the RMN microemulsions were able to penetrate the skin and release hydroxychavicol, achieving a maximum cumulative permeation of 26% over 8 h. All microemulsion formulations containing 0.5%, 1%, and 3% of RMN extract were non-irritating and could be safely applied to human skin. GRAPHICAL ABSTRACT